Comportamento de não consumo de produtos dos patrocinadores de Cruzeiro e Atlético-MG pelos torcedores do clube rival - Felipe Alexandre de Souza Félix Nunes (2020)
Sports marketing has evolved driven by the growth of the sports industry, playing an important role in the dynamics of the industry. Thus the area acquired relevance in the promotion scenario, with studies attesting to the effectiveness of the use of advertising associated with sports, with the practice of sponsorship driving various investments. In this context, as it is the most popular sport in the world, soccer is a vehicle with wide advantage in communicating values to consumers. In fact, the relationship between the fan-consumer, their favorite team and rival teams has motivated studies over the last decade. This project aims to clarify how the polarization between two clubs influences the consumption and non-consumption of sponsored brand products. Coincidence Analysis (CNA) was used as a research approach, in order to understand the various combinations of conditions for a given event, while providing a causal explanation for the phenomenon. It has been proposed to use a calibration for fuzzy sets that has not yet been used in Comparative Configurational Methods. Using the aggregation of the scores, the constitution of the four factors that made up the analysis was dealt with, finding a solution of constitution of rivalry relevant to future works in the area. The relationships between the main factors pointed to the influence of rivalry in the rejection of a product or service manufactured by rival club sponsor, but relevant to the fan's relationship with the club’s own sponsor. The work contributes to future research pointing to the capacity of Coincidence Analysis to model relationships involving constructs of marketing and finding relevant solutions in a concept of non-symmetrical relationships. The managerial implications for this tend to increase the importance of the sponsor's activation and engagement work with the soccer fan, in order to enhance the fan's affection.